Parametric static analysis of a new type of fabricated plate grillard thin shell roof structure. Issue 1 (February 2020) - Liu, Kai; Wu, Xuewen; Zhao, Xueying; Hong, Cheng; Yi, Shuai
Abstract: The new fabricated slab ribbed shell roof structure is a new structure based on a large-span steel-concrete composite thin shell roof. An assembly unit composed of a thin-walled steel ribbed plate, a base plate, and concrete provided with bolt holes, and a plate-grid thin shell roof structure formed by the assembling and connecting assembly units. Considering the influence of the structure's rise span ratio, five groups of rise span ratios were used for finite element analysis and compared with single-layer cylindrical reticulated shells. The analysis shows that the mean value of the ultimate load of the new prefabricated panel latticed thin shell roof structure is increased by 5.3% on average compared with the single-layer cylindrical reticulated shell structure. When the rise span ratio is 1/5, the structure has the largest stiffness and the smallest deformation; when the rise span ratio exceeds 1/5, the growth trend in the ultimate load that the structure can withstand will become smoother, and the average maximum displacement will decrease by 4.3% compared with the single-layer cylindrical reticulated shell, which shows that the grid lattice structure has better stiffness.